Pengaruh Sistem Pemasaran Digital Marketing Dan Promosi Terhadap Keputusan Pembelian Ropang OTW Di Cempaka Putih Jakarta Pusat - Sri Rahayu; Yayak Heriyanto (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This thesis uses quantitative research on the effect of digital marketing and promotion marketing systems on consumer purchasing decisions at Ropang OTW CempakaPutih in Central Jakarta. The data in this study were analyzed using multiple linear regression analysis with t test and f test. The sample was determined using non probability sampling technique. It consisted of 50 customers of Ropang OTW CempakaPutih in Central Jakarta. The variables of this research include the dependent variable, Consumer Purchasing Decision (Y), and the independent variables, the Digital Marketing System (X1) and Promotion (X2).Based on the results of the analysis, a significance value of 0.000 <0.05 was obtained, meaning that the variables of Digital Marketing and Promotion Marketing Systems have an effect on the Consumer Purchasing Decisions variable. The results of the F test with the help of SPSS 24 software show that the variables of Digital Marketing and Promotion Marketing Systems simultaneously affect the Consumer Purchasing Decisions variable with a value of 46.556 and a significance of 0.000. The coefficient of determination of the simultaneous effect of the Digital Marketing and Promotion Marketing Systems variables on the Consumer Purchasing Decision variable is 66.5%, with the remaining 33.5% influenced by other variables not included in the model or equation of this study.